The Conceptualization of War in a Dholuo Gospel Song (The University of Nairobi Journal of Language and Linguistics, 2026)
The paper investigates the discourse processing mechanisms behind the mental representations created by recipients of the gospel song Yesu Tiyo Taling’aling’a ‘Jesus is working, and I am just silent’, by Milka Omondi. The paper uses the analytical tools provided by Text World Theory (TWT), a cognitive linguistics framework for discourse processing (Werth 1999, Gavins 2007), to analyse how world-building and function-advancing elements contribute to the interpretation of the gospel song. This song was chosen for analysis in this paper because of its popularity at social, religious, and political functions in the Luo nation in Kenya. On most occasions, it presents a split discourse world because the singer herself and the recipients/ audience do not share the same physical space. The paper demonstrates how deictic and referential information and function-advancing propositions in the song combine with the listeners’ linguistic, cultural, and general knowledge to facilitate the metaphoric conceptualization of war as work. It also shows that among the five entities/referents named in the song, Yesu ‘Jesus’ is the protagonist of the ongoing war and conflict. The overall aim of the song/text is religious persuasion, as the first-person narrator enacts the recipient and persuades the recipient to accept the ideology that there is a war and that she/he should be silent and let Jesus do the work. This paper contributes to the cognitive linguistic analysis of data from an indigenous language in Kenya. It shows how grammatical structures relate to cognition and cultural expressions in a Dholuo song.
Keywords: Text World Theory; discourse world; world-building elements; function-advancing propositions; cognitive linguistics; Dholuo; Gospel song